The Role of Supervisory Management in the company: Commitment and Planning - Cahyani, Regita; Jessy Angelliza Chantica; Achmad Romadhon (Dinasti Research, 2022)
In a company, it is very crucial to have a Supervisory Management which is authorized to supervise the operational activities of a company. Which will later become a benchmark for a company that is good or not. Supervisory Management is also important for its role in the company, where majority ownership of the company is owned by individuals. For this reason, so that companies can contribute to increasing the APBD, good corporate governance is needed. Including in terms of employee morale at work, planning, employee abilities. This article reviews Supervisory Management Planning in Companies: Commitment and Planning Affecting Supervision Management in Companies, namely: a study of Human Resource Management literature. The purpose of writing this article is to hypothesize the influence between variables to be used in further research. The results of this literature review article are: 1) Commitment has an effect on Supervisory Management in the company and 2) Planning has an effect on Supervision Management in the company.